Meningkatkan Kemampuan Membaca Siswa Melalui Gerakan Literasi di UPTD SMP Negeri 5 Kupang - Leban, Novansius Putra Cu; Akhwan, Maria Elisabet; Tanggela, Hesti Nofita; More, Maria Trisna; Anyi, Putri Chayani; Rohi, Enasely Mega Wenyi (Penerbit Widina, Widina Media Utama, 2025)
The ability to read literacy is a basic aspect that students must have which is used to absorb various sources of information received. The school literacy movement is the ability to access, understand and use things intelligently through various activities, including reading, looking and listening. This research aims to get an overview of the results of the student reading literacy movement and its influence on improving students' reading abilities at UPTD SMP Negeri 5 Kupang. Literacy movement activities are carried out using observatiosn and interviews methods. Media used to support literacy movement activities such as printed books, story books and other reading books. The objects of the research are students who are classified as having low reading literacy abilities. The results of this activity show that the implementation of the school literacy guidance program has a significant positive influence on students' interest in reading, there is an increase in overall interest in reading among students who are the objects of research after active participation in reading activities through literacy guidance at school.ABSTRAKKemampuan literasi membaca adalah aspek dasar yang harus dimiliki oleh siswa yang digunakan untuk menyerap berbagai sumber informasi yang diterima Gerakan literasi sekolah adalah kemampuan mengakses, memahami dan menggunakan sesuatu secara cerdas melalui berbagai aktivitas, antara lain membaca, melihat dan menyimak. Penelitian ini bertujuan untuk mendapatkan gambaran hasil gerakan literasi membaca siswa serta pengaruhnya terhadap peningkatan kemampuan membaca siswa di UPTD SMP Negeri 5 Kupang. Kegiatan gerakan literasi dilakukan dengan metode observasi dan wawancara. Media yang digunakan untuk mendukung kegiatan gerakan literasi seperti, buku-buku cetak, buku cerita dan buku bacaan lainnya. Objek dalam penelitian adalah siswa yang tergolong kemampuan literasi membaca rendah. Hasil kegiatan ini menunjukan implementasi program bimbingan literasi sekolah memiliki pengaruh positif yang signifikan terhadap minat membaca siswa, adanya peningkatan minat membaca secara keseluruhan di antara siswa yang menjadi objek penelitian setelah partisipasi aktif dalam kegiatan membaca melalui bimbingan literasi di sekolah.